Framework for UX Based M-Learning Using Learning Style and Recommendation System - Nimkoompai, Apichaya; Paireekreng, Worapat (International Journal of Informatics and Information Systems, 2020)
M-learning plays the key role in the educational industry is increasingly. However, the current use of M-learning is not designed for individual learner style. Consequently, it causes many students not to understand lessons precisely.Not only learning style which determines the course material but also user interface and interaction called user experience (UX). Therefore, m-learning combined learning style and user experience (UX) are also proposed to learners in order to obtain better understanding towards lessons. This study conducts sample group in basic programming subject with pre-test and modeling students' learning style using Felder & Silverman learning style. The results showed that students' have different learning styles. This prototype of User Experience of M-learning (UXML) related to this subject was developed to deliver the appropriate content match to each student's learning style. This courseware serves 4 patterns of derived learning style they are Active, Sensing, Visual andSequential.Hence, the students are able to understand topic easier from recommended course material with mobility features.